Ernst Ulrich von Weizsäcker A Pioneer on Environmental, Climate and Energy Policies - von Weizsäcker, Ernst Ulrich (SpringerBriefs on Pioneers in Science and Practice, 2014)
On the occasion of the 75th birthday of Ernst Ulrich von Weizsäcker this unique anthology presents thought-provoking texts from 1970 to 2013, spanning several disciplines and combining science and practice. Among them are three Reports to the Club of Rome that Weizsäcker lead-authored, a new university curriculum system to promote interdisciplinary studies and a proposal for a five-fold increase in resource productivity, which would make it possible to shut down nuclear and fossil power plants, avoiding dangerous climate change impacts. Weizsäcker is Co-President of the Club of Rome and Co-Chair of UNEP's Resource Panel. He has served as a Professor of Biology, President of Kassel Univ., Director of the UN Centre for Science and Technology and of the Institute for European Environment Policy, President of the Wuppertal Institute for Climate, Environment and Energy, as a Member of the Bundestag, as Chair of its Environment Committee and as Dean of the Bren School for Environmental Science and Management, Univ. of California, Santa Barbara, USA.